2008
DOI: 10.1177/1078345807308847
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Mycobacterium tuberculosis in a Tennessee Prison, 2002-2004

Abstract: An outbreak investigation was conducted in a Tennessee prison to determine the extent of Mycobacterium tuberculosis transmission and prevent additional tuberculosis (TB) cases. Inmates, staff, visitors, and community contacts were screened. TB disease was diagnosed for eight inmates, including one after release and three people in the community, including two young children. In addition, 59 contacts (47 inmates, 4 staff members, and 8 additional persons in the community) were newly diagnosed with latent TB inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 23 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…58,24,32 During the 1990s, one county in New York diagnosed 40 TB cases among current or former inmates, 1 case in a correctional officer, and 8 cases among individuals exposed in the community. 5 In more recent TB outbreaks that have spread from the state prison system to communities in Arkansas 4 and Tennessee, 6 inmates either had been released before treatment of latent TB infection could be completed 4 or were known to have been recently infected but did not receive treatment. 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…58,24,32 During the 1990s, one county in New York diagnosed 40 TB cases among current or former inmates, 1 case in a correctional officer, and 8 cases among individuals exposed in the community. 5 In more recent TB outbreaks that have spread from the state prison system to communities in Arkansas 4 and Tennessee, 6 inmates either had been released before treatment of latent TB infection could be completed 4 or were known to have been recently infected but did not receive treatment. 6 …”
Section: Discussionmentioning
confidence: 99%
“…5 In more recent TB outbreaks that have spread from the state prison system to communities in Arkansas 4 and Tennessee, 6 inmates either had been released before treatment of latent TB infection could be completed 4 or were known to have been recently infected but did not receive treatment. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 55 57 Stigma against PIP and limited appreciation of the permeability of prisons to surrounding communities can act as potential obstacles to their inclusion in the public health infrastructure. 56 62 63 70 Interagency collaboration Interagency collaboration is integral to managing infectious disease outbreaks. 44 50 56 60 63 64 66-70 Studies described early establishment of a designated interagency group to coordinate the response, 60 involving prison staff, the local state health department, public health laboratory, public health unit and hospital services.…”
mentioning
confidence: 99%
“…8,10–16 Lapses in TB prevention and control measures, including incomplete TB treatment, have further contributed to TB outbreaks at facilities, resulting in TB transmission to the surrounding communities in some instances. 10–12,14,15,17,18 An estimated 9%–43% of TB cases in the community have been shown to be associated with incarceration. 10,19,20 One review of source cases that started TB outbreaks in the U.S. showed that 50% of source cases were among people with a history of incarceration at some point in the past.…”
Section: Introductionmentioning
confidence: 99%